Sarcoidosis diagnosed on granulomas in the explanted heart after transplantation: Results of a French nationwide study. (15th May 2020) - Chazal, Thibaud; Varnous, Shaida; Guihaire, Julien; Goeminne, Céline; Launay, David; Boignard, Aude; Vermes, Emmanuelle; Dorent, Richard; Camilleri, Lionel; Lelong, Bernard; Epailly, Eric; Lebreton, Guillaume; et al.
Abstract: Background: Cardiac sarcoidosis (CS) is a challenging diagnosis. Patients may progress to end-stage congestive heart failure and require cardiac transplantation without ever having been diagnosed. Characteristics and outcomes of patients with granulomas in the explanted hearts are unknown. Methods: All French heart transplantation centers were contacted to participate in the study. Each center searched through local databases for the cases of non-caseating granuloma in the explanted hearts between 2000 and 2017. Data before and after transplantation were recorded from medical charts. Survival of CS and all- cause heart transplantation patients were compared. Results: Fifteen patients (10 men, 5 women) received a diagnosis of CS based on pathologic data of the explanted heart and were recruited for the study. All patients were diagnosed as non-ischemic dilated or hypertrophic cardiomyopathy and presented congestive heart failure. Eight patients (53%) had ventricular rhythm disturbances, and 3 (20%) a complete heart block. Ten out of 13 patients (77%) had extracardiac radiological signs compatible with sarcoidosis on chest computed tomography (CT) scans. One patient died 3 months after transplantation from infectious complications. The 14 remaining patients were still alive at the end of the study (median follow-up of 28.8 months). One patient had a second heart transplantation 5 years later because of chronic allograft vasculopathy. One patient presented a relapse of CS confirmed by myocardial biopsies 9 years after transplantation, requiring an escalation of immunosuppressive therapy. Conclusion: CS may be undiagnosed before heart transplantation. In 77% of cases, sarcoidosis could have been detected before transplantation with non-invasive imaging techniques. Highlights: Cardiac sarcoidosis may be undiagnosed before heart transplantation. In 77% of cases, sarcoidosis could have been detected before transplantation with non-invasive imaging techniques. Long term outcomes of sarcoidosis after cardiac transplantation are similar to those of all-cause transplantations recipients.